WAKTU PAPARAN GAS OZON TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Amal Ma’ruf; Sri Sinto Dewi; Fandhi Adi Wardoyo (Universitas Muhammadiyah Semarang, 2017)
Ozone is one of the gases that can be used as a disinfectant to inhibit the growth of Escherichia coli bacteria. Time of exposure to ozone gas is a way used to disinfectEscherichia coli bacteria. The purpose of this study was to observe the number ofEscherichia coli bacteria exposed to ozone gas with exposure time of 5, 10, 15, 20, 25and 30 minutes and ozone gas control. The study sample was Escherichia colibacteria exposed to ozone gas. The results of the number of colonies of Escherichiacoli on CCA media after exposure to 5, 10, 15 minutes of ozone gas were mean 2.5 x106, 1.25 x 106, 0.5 x 106 CFU / ml, and 20, 25, 30 minutes there is no bacterialgrowth. Control or no exposure to ozone gas mean is 9 x106 CFU / ml. The time ofexposure to ozone gas is most effective in killing Escherichia coli bacteria ie at 20minutes.Keywords: ozone gas, Escherichia coli, Exposure time.